2017
DOI: 10.1016/j.worlddev.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

To Specialize or Diversify: Agricultural Diversity and Poverty Dynamics in Ethiopia

Abstract: Recent agricultural development policies have begun to shift focus from the promotion of a few staple crops toward encouraging crop diversity. The belief is that crop diversification is an effective strategy for dealing with a variety of issues, including poverty alleviation. However, there is a lack of empirical evidence to justify these positions. We contribute to filling this research gap by providing quantitative evidence on the impact of diversity in crop cultivation on household poverty. Using household … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(87 citation statements)
references
References 47 publications
6
70
0
Order By: Relevance
“…Attention has been largely focused on agricultural intensification as a mechanism for producing more, even though food insecurity in many places is largely an income and distribution problem (Hazell & Wood, ). Also, there has been much less research focusing on the contribution of farming diversity toward achieving food security, despite evidence that more diverse agroecosystems are likely to perform better today and under changing environmental conditions because a broader range of functions and responses to change will stabilize the system (Altieri, ; Lin, ; Michler & Josephson, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention has been largely focused on agricultural intensification as a mechanism for producing more, even though food insecurity in many places is largely an income and distribution problem (Hazell & Wood, ). Also, there has been much less research focusing on the contribution of farming diversity toward achieving food security, despite evidence that more diverse agroecosystems are likely to perform better today and under changing environmental conditions because a broader range of functions and responses to change will stabilize the system (Altieri, ; Lin, ; Michler & Josephson, ).…”
Section: Introductionmentioning
confidence: 99%
“…agroecosystems are likely to perform better today and under changing environmental conditions because a broader range of functions and responses to change will stabilize the system (Altieri, 1999;Lin, 2011;Michler & Josephson, 2017).…”
mentioning
confidence: 99%
“…Such farms introduce the risk of a single disease destroying an entire harvest, especially when only one genetic variety is present [30,31]. In addition, farm diversification has benefits which include poverty alleviation [32,33], increased profitability [34], improved food security [35], and decreased yield variability [36].…”
Section: Farm Diversification Metricsmentioning
confidence: 99%
“…Studies have shown that crop diversity contributes to resilience through a type of “insurance” where a failure in one crop is mitigated by another crop/cultivar and also through more efficient resource partitioning at various scales [5, 19, 20]. As such, crop diversification has been shown to be beneficial to building climate resilience in many countries such as in China [21], Canada [22], Kenya [23], Ethiopia [24], Malawi [9, 18], Zimbabwe [25] and also Ghana, [26, 27]. Crop diversification is achieved through multiple cropping where farmers grow two or more crops in sequence (relay cropping) or together (intercropping and mixed cropping) within the same year.…”
Section: Introductionmentioning
confidence: 99%